Aerobic Exercise Training in Formerly Preeclamptic Women. Issue 5 (November 2015) - Scholten, Ralph R.; Hopman, Maria T.E.; Lotgering, Fred K.; Spaanderman, Marc E.A.
<x xml:space="preserve">Abstract</x> In women with a history of preeclampsia, low plasma volume (⩽1373 mL/m2) is associated with recurrent preeclampsia and chronic hypertension. Interventions that improve volume reserve may reduce these risks in formerly preeclamptic women. In this study, we examined the effects of aerobic exercise training on venous reserves in 24 normotensive formerly preeclamptic women and 20 controls. Before and after 12-week aerobic exercise training, we measured plasma volume with albumin indicator dilution technique and venous compliance with venous occlusion plethysmography. Venous compliance and hemodynamic responses were assessed dynamically during graded head-up tilt (HUT). Formerly preeclamptic women had lower pretraining plasma volume and venous compliance than controls (1348±78 versus 1529±112 mL/m2; P<0.01 and 0.04±0.02 versus 0.07±0.01 mL·dL−1·mm Hg−1; P<0.01, respectively). Blood pressure decreased comparably between groups in response to HUT (P=0.11); the increase in heart rate in response to HUT was however more pronounced in preeclamptic women than in controls (P=0.01) Training increased plasma volume comparably in both groups (+180 versus +135 mL/m2, P=0.22) and similarly physical fitness (+3.4 and +3.7 mL·min−1·kg−1, P=0.43). Venous compliance increased twice as much in formerly preeclamptic women than in controls (supine +0.02 versus +0.01 mL·dL−1·mm Hg−1; P<0.01). After training, HUT decreased mean blood pressure comparable with pretraining responses in both groups, whereas both groups fulfilled the HUT testing at a persistently lower heart rate. These results demonstrate that 12 weeks of aerobic exercise training improve venous reserve in postpartum women. Training normalized plasma volume and venous compliance in formerly preeclamptic women to pretraining levels of controls. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00900458.